Fixed return green sukuk ijarah: Normative-philosophical analysis hifdz al-mal and hifdz al-bi'ah for ecological stability - Rahmawati, Ai; Ummah, Shofiyatul; Mathar, Ahmad Rifat (Kemakmuran Hijau: Jurnal Ekonomi Pembangunan, 2026)
Background: Green sukuk has emerged as a strategic Islamic financial instrument that integrates economic development with environmental preservation while reflecting the contemporary application of Sharia principles in sustainable finance. This study aims to examine the normative and philosophical validity of fixed return guarantees in ijarah-based green sukuk through the perspectives of hifdz al-māl (protection of wealth) and hifdz al-bī’ah (protection of the environment), building on prior studies that discuss green Islamic finance, sukuk structures, and maqasid-oriented investment models. Methods: Using a normative-philosophical approach, this research analyzes classical jurisprudential principles, contemporary regulatory frameworks, and conceptual discourse on Sharia-compliant sustainability finance. Findings: The study finds that fixed return guarantees can reduce market volatility risks and enhance the continuity of renewable energy and climate-related projects, thereby aligning with Sharia objectives of safeguarding assets through accountable fund management and promoting environmental sustainability through support for green initiatives. The results also demonstrate coherence between the theoretical framework of maqasid al-sharia and the practical structure of ijarah green sukuk. Conclusion: Fixed return guarantees in ijarah-based green sukuk are normatively acceptable and philosophically compatible with the goals of economic resilience and ecological balance in Islamic finance. Novelty/Originality: This article offers an integrative assessment of fixed return mechanisms in green sukuk through a dual maqasid lens, establishing a new theoretical linkage between asset protection and environmental preservation within Sharia-compliant investment structures.